Exploring the Meaning of Life in Individuals Suffering from Thalassemia - Skolastika Febriana Anggraini; Arthur Huwae (Kuras Institute, 2026)
People with Thalassemia live their lives with blood transfusions and take medication for the rest of their lives. This study aims to explore the meaning of life in individuals suffering from Thalassemia. The experience as an individual suffering from Thalassemia disease and the life meaning that the three participants achieved were explored qualitative, which was further analyzed using Interpretive Phenomenological Analysis (IPA). Participants were determined by the nonprobability sampling technique, which is purposive sampling with certain considerations as a sample and data source with the characteristics of individuals suffering from Thalassemia between 13-35 years old who have been diagnosed with Thalassemia disease since birth and always have blood transfusions at least 1 time a week. The themes that emerge from the three dimensions of the meaning of life are the personal, social dimensions and the dimensions of values. The life lived can make individuals feel more meaningful when they are able to accept their circumstances, live their routines well and do what they like and are considered goals. The findings of this study help individuals suffering from Thalassemia disease broadly to be more self-accepting, dare to have life goals and achieve them by still doing blood transfusions and taking medication regularly. The importance of structured psychosocial support, meaning-based counseling, and inclusive policies for individuals suffering from Thalassemia disease as well as enriching the understanding of the construction of life meaning through a phenomenological-interpretive approach that uncovers the role of cultural factors and subjective dynamics in dealing with chronic disease.